Sorption isotherms and thermodynamic properties of wheat malt under storage conditions - Silva, Kamilla Soares [UNESP]; Polachini, Tiago Carregari [UNESP]; Luna-Flores, Mario; Luna-Solano, Guadalupe; Resende, Osvaldo; Telis-Romero, Javier [UNESP] (Wiley, 2021)
The growing use of wheat malt in food applications has boosted studies regarding suitable conditions for processing and storage. Because water sorption during storage may affect the malt functionality, sorption isotherms of wheat malt were determined aiming at covering a wide range of temperatures (10–40°C) and relative humidity (5.80–98.18%). Different theoretical models were fitted to the experimental data. Thermodynamic properties as heat of sorption, enthalpy, entropy, and Gibbs free energy were evaluated. Equilibrium moisture content tended to increase with increasing water activity and decreasing temperature. Henderson and GAB models showed the best fit for wheat malt isotherms. Isosteric heat of sorption increased as the moisture content decreased. Differential enthalpy (−1,071.82 to −36.95 kJ/kg) and entropy (2.29 to 0.12 kJ/k/K) values were linearly dependent, meeting the requirements to confirm the compensation theory. Water adsorption of wheat malt was considered as an enthalpy-driven (ΔH < 0) and spontaneous process (−324.13 kJ/kg< ΔG < −0.13 kJ/kg). Reported data can be useful for designing adequate storage conditions of wheat malt. Practical Applications: Wheat malt has been widely used together with or in replacement of barley malt in many food applications, from brewing to ingredient industries. As a consequence of the seasonality, wheat malt should be stored for long periods to ensure the supply chain over the year. As seen as the storage conditions may affect the quality and shelf-life of wheat malt, this work aimed at: reporting experimental conditions to better preserve the malt quality and make viable its long-term usage in different food applications; determining and evaluating its water sorption properties in a range of temperatures and relative humidity; providing mathematical models and thermodynamic analysis for designing adequate storage conditions.